Perancangan sistem pencatatan keuangan dan perpajakan sederhana berbasis excel sesuai SAK EMKM Untuk mendukung akuntabilitas pada UMKM ayam kremes shazan - Adinda, Tria Nur; Yuliansyah, Dwi Novrian (LP2M Politeknik Jambi, 2026)
This study aims to design and implement a simple Excel-based financial and tax recording system in accordance with SAK EMKM to improve financial accountability at UMKM Ayam Kremes Shazan. The case study approach was used with an Excel system to record sales, purchases, and operational expenses, calculate profit and loss, and facilitate final income tax (PPh Final 0.5%) according to Government Regulation No. 23 of 2018. The results show the system simplifies transaction recording, reduces the risk of mixing personal and business funds, and improves accuracy and efficiency in calculating balances, profit and loss, and taxes. It also enables transparent financial reports, including general ledger, trial balance, profit and loss statements, and balance sheets, allowing informed business decisions. In conclusion, the Excel system enhances financial management quality, transparency, and accountability, supports effective decision-making, and promotes sustainable business growth. Consistent recording, improved Excel skills, and further system development are recommended.Keywords: MSMEs, Financial Accountability, Excel, SAK EMKM, PPh Final 0.5%